FEAR OF MISSING OUT DAN PSYCHOLOGICAL WELL-BEING PADA INDIVIDU USIA EMERGING ADULTHOOD - Nur Ainiyah; Listyati Setyo Palupi (Program Studi Psikologi Universitas Malahayati, 2022)
ABSTRACT: FEAR OF MISSING OUT AND PSYCHOLOGICAL WELL BEING IN EMERGING ADULTHOOD INDIVIDUAL The group that dominates today's use of social media and the internet is emerging adulthood. Meanwhile, several studies show that excessive use of social media can cause negative effects, one of which is on the level of psychological well-being as a result of fear of missing out. The goal of this study is to see if there is a link between fear of missing out and psychological well-being in emerging adults. The Fear of Missing Out measure and the Javanese Psychological Well-being Scale were used in this quantitative study, which included 226 participants aged 18 to 25 years old (39 males; 187 females). To see the relationship between the two variables researchers used parametric analysis using Pearson Product Moment. The findings of this study show a negative correlation value (r (224) = -.324; p< .001), implying that as the fear of missing out grows, so does psychological well-being.The implication of this study is to show the need to pay attention to the psychological well-being of individuals by managing the use of social media so that they do not have a negative impact on the level of individual psychological well-being..Keywords: Emerging Adulthood, Fear of Missing Out, Psychological Well-Being Individu usia emerging adulthood merupakan kalangan yang mendominasi penggunaan media sosial dan internet saat ini. Sementara itu, beberapa studi menunjukkan bahwa penggunaan media sosial yang berlebihan dapat menyebabkan efek negatif salah satunya terhadap tingkat psychological well-being akibat dari adanya fear of missing out. Penelitian ini bertujuan untuk mengetahui hubungan antara fear of missing out dengan psychological well-being pada individu usia emerging adulthood. Penelitian kuantitatif dengan menggunakan skala Fear of Missing Out dan Skala Javanese Psychological Well-being ini melibatkan 226 partisipan berusia 18-25 tahun (39 laki-laki; 187 perempuan). Untuk melihat hubungan antara kedua variabel peneliti menggunakan analisis parametrik dengan menggunakan Pearson Product Moment. Hasil penelitian ini menunjukkan nilai korelasi negatif (r (224)= -.324; p< .001) yang artinya jika fear of missing out meningkat maka psychological well-being akan menurun. Implikasi pada penelitian ini adalah perlunya memperhatikan psychological well-being individu dengan melakukan manajemen penggunaan media sosial agar tidak berdampak negatef terhadap tingkat psychological well-being individu. Kata Kunci: Usia Emerging Adulthood, Fear of Missing Out, Psychological Well-Being